Effect of linalool on the acquisition and reinstatement of morphine-induced conditioned place preference in mice - Narjes Pourtaqi; Mohsen Imenshahidi; Bibi Marjan Razavi; Hossein Hosseinzadeh (Mashhad University of Medical Sciences, 2017)
Objective: The effect of linalool, a terpene alcohol found in many plants, which inhibits NMDA receptors, on the acquisition and reinstatement of morphine-induced conditioned place preference (CPP) was evaluated in mice.Material and Methods: The effects of different doses of linalool (12.5, 25 and 50 mg/kg, i.p.), memantine (20 mg/kg, an NMDA receptor antagonist) and saline, in CPP induced by 40 mg/kg of morphine were investigated in mice. In another experiment, a single injection of morphine (10 mg/kg) reinstated the place reference following extinction of a place preference induced by morphine (40 mg/kg). Linalool (12.5, 25 and 50 mg/kg, i.p.), memantine (20 mg/kg) and saline were administrated 30 min before this priming dose of morphine.Results: In the first experiment, linalool (12.5 and 50 mg/kg) was able to decrease morphine-induced CPP. In the second part, linalool (25 and 50 mg/kg) reduced morphine-induced reinstatement of place preference. Both acquisition and reinstatement of morphine-induced CPP, were considerably decreased by memantine.Conclusion: The present study showed that linalool is able to reduce the acquisition and reinstatement of morphine-induced CPP which might be due tothrough NMDA receptors blocking.